Pembangkit Listrik Tenaga Surya Atap untuk Sumber Energi Listrik Rumah Kebun: Rooftop Solar Power Plants for Garden House Electrical Energy Sources - Mangelep, Indriani; Rumbayan, Meita; Mangindaan, Glanny (Jurnal Teknik Elektro dan Komputer, 2023)
Abstract — Electricity has become a basic need for society, the need for electricity is not only for needs in homes, offices or other large buildings, but electricity is also needed in small places, one of which is in a garden house. The plantations that are close to the PLN electricity pole have received electricity supply, but there are still many garden houses that have not yet received electricity from the PLN because the distance between the electricity pole and the garden house is very far. This research has a goal to create a system, namely rooftop solar power as a source of electrical energy for garden houses. From this study, several results and conclusions were obtained, namely that the implementation of rooftop PLTS for garden houses had been carried out properly, and measurements had been carried out several times and for the measurement results the largest electrical energy was 340.8 Wh.      Keywords — Electrical Energy; Garden House; Roof PLTS; Watt Meters   Abstrak — Listrik sudah menjadi kebutuhan pokok masyarakat, kebutuhan akan listrik tidak hanya untuk kebutuhan yang ada di rumah, perkantoran, atau bangunan besar lainnya, melainkan listrik juga dibutuhkan di tempat-tempat kecil, salah satunya di rumah kebun. Kebun yang jaraknya dekat dengan tiang listrik PLN sudah mendapat pasokan listrik, namun masih banyak rumah kebun belum mendapat pasokan listrik dari PLN karena jarak tiang listrik dengan rumah kebun sangat jauh. Penelitian ini memiliki tujuan untuk membuat suatu sistem yaitu PLTS atap sebagai sumber energi listrik rumah kebun. Dari penelitian ini didapat beberapa hasil dan kesimpulan yaitu bahwa implementasi PLTS atap untuk rumah kebun telah dilaksanakan dengan baik, dan telah dilakukan beberapa kali pengukuran dan untuk hasil pengukuran energi listrik terbesar yaitu 340,8 Wh.   Kata kunci — Energi Listrik; PLTS Atap; Rumah Kebun; Watt Meter